Clinical Characteristics of Fuchs’ Uveitis Syndrome - Nalçacıoğlu, Pınar (Turk J Ophthalmol, 2016)
OBJECTIVES: To evaluate the clinical and demographic properties of Fuchs’ uveitis syndrome (FUS) in Turkish patients. MATERIALS AND METHODS: The medical records of 161 patients with FUS followed in the Uveitis Division of Ulucanlar Eye Hospital between 1996 and 2014 were respectively reviewed. The mean age at diagnosis, sex, the number of affected eyes, follow-up period, clinical findings at presentation, complications during the follow-up period, medical and surgical treatments, and best corrected visual acuity at the initial and final visits were recorded. RESULTS: The study included 171 eyes of 161 patients diagnosed with FUS. Of the patients, 94 (58.4%) were female and 67 (41.6%) were male. The mean age at presentation was 35.2±11.0 (11-65) years. The mean follow-up period was 23.5±32.8 (2-216) months. Ten (6.2%) patients had bilateral involvement. The most common symptoms at presentation were decreased visual acuity or blurred vision in 63 (39.1%) and floaters in 19 (11.8%) patients. Clinical findings at presentation included diffuse small, round, white keratic precipitates in 128 (74.8%) eyes, anterior chamber reaction in 82 (47.9%), vitreous cells in 122 (71.3%), heterochromia in 47 (27.4%) and iris nodules in 32 (18.7%) eyes. During the follow-up period, elevated intraocular pressure occured in 31 (18.1%) eyes and the most common complication was cataract development (89 eyes, 52.0%). CONCLUSION: Heterochromia was observed in 27.4% of patients in our study. However, the diffuse small, round keratic precipitates, low-grade anterior chamber reaction and varying degrees of vitreous reaction are more common clinical characteristics that are helpful in making the diagnosis.